2022
DOI: 10.3390/d14121142
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Fish Richness in the Yarlung Zangbo River Basin

Abstract: Global warming significantly affects plateau glaciers and surface runoff, and fish are bound to be severely affected. Additionally, an increasing number of human activities (e.g., free captive animals, aquaculture) have led to vulnerable plateau ecosystems being affected by invasive species. To address the above issues, we collected the currently published fish distribution data, and for the first time constructed a richness and fluvial system distribution map of the Yarlung Zangbo River fish (4 orders, 10 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For example, Ruiz-Navarro et al [30] reported the annual mean temperature and mean diurnal range of temperature as the most important climatic variables indicating the suitable habitat of Perca fluviatilis and Esox lucius in Great Britain. The study of Li et al [55] indicated that environmental factors related to precipitation, such as precipitation of seasonality, play a significant role in the establishment success of non-native fishes across the Yarlung Zangbo River Basin in the Tibetan Plateau.…”
Section: Ensemble Model Evaluation and Dominant Climatic Factormentioning
confidence: 99%
“…For example, Ruiz-Navarro et al [30] reported the annual mean temperature and mean diurnal range of temperature as the most important climatic variables indicating the suitable habitat of Perca fluviatilis and Esox lucius in Great Britain. The study of Li et al [55] indicated that environmental factors related to precipitation, such as precipitation of seasonality, play a significant role in the establishment success of non-native fishes across the Yarlung Zangbo River Basin in the Tibetan Plateau.…”
Section: Ensemble Model Evaluation and Dominant Climatic Factormentioning
confidence: 99%
“…It is necessary to make full use of the advantage of large water level difference in the main stream of the Yarlung Zangbo River to build a series of multi-step hydropower plants. Hydroelectric power generation is a renewable energy with small impact on the environment, high power generation efficiency and low power generation cost [4][5].…”
Section: Introductionmentioning
confidence: 99%